A coopera????o t??cnica internacional como mecanismo para o aprimoramento da gest??o ambiental: Corredor Ecol??gico do Cerrado Paran??-Pireneus - Ichikawa, Paulo Eiryo (2010)
This study aims to analyze international technical cooperation as a mechanism for improving environmental management. Using the case study method as a research strategy, this work presents a pool of activities on technical cooperation carried out by Japan and Brazil, in the Brazilian Cerrado bioma, from 1998 to 2006. Through theories of International Relations, this research will examine how extent international technical cooperation can contribute to improving environmental management. Thus, the components are emphasized to promote the realization and implementation of an international technical cooperation project targeting the conservation of biodiversity through transfer of knowledge applied to ecological corridors. Also, the difficulties presented in cooperation???s activities are highlighted. Accordingly, the present study aims to contribute to the studies of international cooperation and environmental issues. To be specific, it deals with international technical cooperation can contribute to environmental management.